2020
DOI: 10.1111/jace.17157
|View full text |Cite
|
Sign up to set email alerts
|

Broadband near‐infrared emission enhancement in K2Ga2Sn6O16:Cr3+phosphor by electron‐lattice coupling regulation

Abstract: Cr3+‐doped phosphors have recently gained attention for their application in broadband near‐infrared phosphor‐converted light‐emitting diodes (pc‐LEDs), but generally exhibit low efficiency. In this work, K2Ga2Sn6O16:Cr3+ (KGSO:Cr) phosphor was designed and synthesized. The experimental results show that the Cr3+‐doped phosphor exhibited broadband emissivity in the range 650‐1300 nm, with a full width at half maximum (FWHM) of approximately 220‐230 nm excited by a wavelength of 450 nm. With the co‐doping of Gd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Meanwhile,the PL intensity and FWHM vary with increasing degree of cosubstitution (y), as shown in Figure 2d.O verall, the PL intensity is enhanced by forming asolid solution (y > 0.20), reaching am aximum at y = 0.50, which is 2.3 times higher than that of the initial LISO:Cr 3+ .E vidently,Z n 2+ incorporation can induce lattice distortion owing to the difference in radius.I th as been reported that proper lattice distortion can introduce an uneven symmetrical field that facilitates breaking of the forbidden transition of Cr 3+ , thereby realizing improved luminescence. [14] In addition, the reduced Stokes shift indicates less non-radiative transition, which also contributes to the enhanced NIR emission. The FWHM value varies in the range of 216-235 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile,the PL intensity and FWHM vary with increasing degree of cosubstitution (y), as shown in Figure 2d.O verall, the PL intensity is enhanced by forming asolid solution (y > 0.20), reaching am aximum at y = 0.50, which is 2.3 times higher than that of the initial LISO:Cr 3+ .E vidently,Z n 2+ incorporation can induce lattice distortion owing to the difference in radius.I th as been reported that proper lattice distortion can introduce an uneven symmetrical field that facilitates breaking of the forbidden transition of Cr 3+ , thereby realizing improved luminescence. [14] In addition, the reduced Stokes shift indicates less non-radiative transition, which also contributes to the enhanced NIR emission. The FWHM value varies in the range of 216-235 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[ 21–23 ] Moreover, this type of emission can be realized by simply doping Cr 3+ ions into a weak octahedral crystal field environment. Therefore, several Cr 3+ activated phosphors for LEDs have been developed, [ 18,24–30 ] some of which exhibit high photoluminescence internal quantum efficiency (IQE) of >90%, such as Gd 3 Sc 2 Ga 3 O 12 :0.01Cr 3+ ,0.5Al 3+ (IQE = 98.6%), [ 31 ] Ca 3 Sc 2 Si 3 O 12 :0.06Cr 3+ (IQE = 92.3%), [ 32 ] and GdAl 3 (BO 3 ) 4 :0.01Cr 3+ (IQE = 91%). [ 33 ] However, the external quantum efficiency (EQE) of these phosphors is limited to 28%, owing to the relatively low absorption efficiency (AE) of Cr 3+ resulting from the parity‐forbidden 3d‐3d electronic transition.…”
Section: Introductionmentioning
confidence: 99%
“…The cosubstitution of [Zn 2+ –Zn 2+ ] for [Li + –In 3+ ] causes contraction of the In−O bond (Figure S9), which increases the D q value according to the relationship of D q vs. 1/R 5 [16] . The nephelauxetic effect has a considerable effect on the Racah parameter, which is negatively related to the electronegativity of the ions [14a, 17] . The average cation electronegativity increases when Li + and In 3+ are substituted by Zn 2+ (Table S5), leading to a decreased B value.…”
Section: Resultsmentioning
confidence: 99%